2009
DOI: 10.1073/pnas.0903691106
|View full text |Cite|
|
Sign up to set email alerts
|

Inclusion formation and neuronal cell death through neuron-to-neuron transmission of α-synuclein

Abstract: Fig. 2.Transformants releasing E␤C suffered less damage than control lines when EPNs were present. (A) Root damage measured on plants that had received neither WCR eggs nor nematodes was minimal, and there was no difference between transformed and nontransformed plants (n ϭ 5, P ϭ 0.87). (B) Root damage on plants that received only WCR eggs, but no nematodes, was substantial. Again, no significant difference was found between the transformed and nontransformed plants (n ϭ 5, P ϭ 0.18). (C) In plots that receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
1,289
3
27

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,348 publications
(1,367 citation statements)
references
References 32 publications
(37 reference statements)
48
1,289
3
27
Order By: Relevance
“…In one case, neural stem cells were transplanted into transgenic mice expressing human α-synuclein. Human α-synuclein was detected in the grafted tissue as rapidly as 1 week after transplantation [33]. This was most consistent with α-synuclein transfer between neurons in vivo.…”
Section: Spread Of α-Synuclein Pathology To Young Neurons In Human Pasupporting
confidence: 72%
See 3 more Smart Citations
“…In one case, neural stem cells were transplanted into transgenic mice expressing human α-synuclein. Human α-synuclein was detected in the grafted tissue as rapidly as 1 week after transplantation [33]. This was most consistent with α-synuclein transfer between neurons in vivo.…”
Section: Spread Of α-Synuclein Pathology To Young Neurons In Human Pasupporting
confidence: 72%
“…This concept was further tested in numerous rodent models using viral expression of human α-synclein [30,31] and transgenic mouse models of PD [32,33]. In one case, neural stem cells were transplanted into transgenic mice expressing human α-synuclein.…”
Section: Spread Of α-Synuclein Pathology To Young Neurons In Human Pamentioning
confidence: 99%
See 2 more Smart Citations
“…the intercellular transfer of misfolded proteins has recently been demonstrated in several neurodegenerative diseases, including aLS [1][2][3], and it has been suggested that this mechanism is responsible for the progressive spread of pathology. Mutations in SOD1 (Cu/Zn-superoxide dismutase) cause 20 % of familial aLS, and these cases display similar clinical features and pathogenesis to sporadic aLS, which accounts for 90 % of all aLS cases.…”
Section: Introductionmentioning
confidence: 99%